Sensing the virus. How social capital enhances hoteliers' ability to cope with COVID-19. (April 2021) - Visentin, Marco; Reis, Rosana Silveira; Cappiello, Giuseppe; Casoli, Debora
Highlights: Hotels' reaction to COVID-19 is driven by social capital and problem-solving. We measure hotel managers' sensemaking and ability to change their service. Hotels' network of relationships helped sense the crisis and change the service. Involvement in the network negatively moderated the effect of social capital. Due to the COVID-19 pandemic, existing problem-solving routines were of little use. Abstract: In this study, we propose a broad conceptual model that incorporates social capital dimensions and problem-solving routines to understand the determinants behind hotel managements' perception of and ability to cope with the COVID-19 pandemic—and thus, to innovate their service offering. We provide empirical support for the notion that, due to uncertainty about reopening after lockdown, the hospitality sector has found existing problem-solving routines to be of little use. Although the local community has been unable to form a shared vision around the pandemic, hoteliers have nevertheless relied on their network of relationships to sense the crisis and find their own ways to adapt. Interestingly, we find that overreliance on trustworthy relationships can diminish the ability to sense a crisis objectively. Our results not only shed light on sensemaking in the hotel industry, but also grapple with the theoretical nature of sensemaking as a socially constructed process.